Modeling and optimization of a shell and louvered fin mini-tubes heat exchanger in an ORC powered by an internal combustion engine. (1st September 2015) - Mastrullo, Rita; Mauro, Alfonso William; Revellin, Rémi; Viscito, Luca
Highlights: New ORC HEX design. Dedicated model. On-road uses. Simulations for real ICEs' conditions. Abstract: Waste heat recovery from exhaust gases of internal combustion engines (ICEs) is an interesting option to increase energy conversion efficiency, especially on on-road applications. Organic Rankine cycles (ORCs) fit well the temperature levels available. Current research interests are devoted to the definition of new design solutions to improve each part of the energy conversion process. Concerning the heat recovery, new concepts for heat exchangers are required to reduce their weight, the refrigerant charge and the related environmental concerns. At the same time, a high performance of the whole system must be kept. In this paper, a new design is introduced related to a shell and louvered fin mini-tubes heat exchanger. Modeling and simulation results are presented to define an optimal design in the whole map of working conditions for a heavy duty diesel engine and a light duty gasoline engine, in order to maximize the overall system efficiency (ORC+ICE). The length and weight of the heat exchanger are consistent with the use in automotive and truck applications, while an increase of the overall system efficiency up to 9% can be achieved.